P- Hydroxybenzyl Alcohol Alleviates Oxidative Stress in a Nonalcoholic Fatty Liver Disease Larval Zebrafish Model and a BRL-3A Hepatocyte Via the Nrf2 Pathway - An, Jing; Cheng, Lijun; Yang, Liping; Song, Nali; Zhang, Ju; Ma, Kejian; Ma, Ji (Frontiers in Pharmacology, 2021)
Nonalcoholic fatty liver disease (NAFLD) as the the most common chronic liver disease gradually become the main burden of disease in the world. However, as the NAFLD has complex pathogenesis such as dyslipidemia, oxidative stress, inflammation and so on, which brings to a large challenge for drugs development, there is still no drug proved by FDA in market to treat the disease. GAS and HBA are active ingredients of Gastrodia elata, have effects in ameliorating nervous system diseases by anti-oxidative stress. HBA is a metabolite of GAS and GAS could perform lipid regulating and improving oxidative stress on HCD induced NAFLD larval zebrafish as previous studies reported, therefore we explored the role of HBA in lipid-regulating and oxidative stress on HCD induced NAFLD larval zebrafish in vivo and FFA-induced BRL-3A hepatocyte in vitro. The gene expression of lipogenesis, inflammation, oxidative stress was measured to investigate the underline mechanism of HBA, the potential target of HBA was explored by immunofluorescence. Altogether, our data highlights HBA has the role in improving NAFLD by lipid-lowering and anti-oxidative via Nrf2/HO-1 signaling pathway, and provided a potential therapeutic compound for NAFLD treatment.